Aldosterone Synthesis and Cytokine Production in Human Peripheral Blood Mononuclear Cells - Ryuzea Miura; Kazufumi Nakamura; Daiji Miura; Aya Miura; Kenichi Hisamatsu; Masahito Kajiya; Katsushi Hashimoto; Satoshi Nagase; Hiroshi Morita; Kengo Fukushima Kusano; Tetsuro Emori; Kazuhiko Ishihara; et al. (Elsevier, 2006)
Previously, we reported that spironolactone reduced cytokine production in cultured human peripheral blood mononuclear cells (PBMCs) with angiotensin (Ang) II stimulation. To address the mechanisms underlying this effect, we examined the contribution of aldosterone to cytokine production in cultured human PBMCs with Ang II stimulation. PBMCs expressed the messenger RNA (mRNA) of Ang II type 1 receptor (AT1R) and mineralocorticoid receptor (MR) both spontaneously and after Ang II stimulation, but expressed Ang II type 2 receptor (AT2R) under neither condition. After 24 h of incubation, exogenous Ang II induced the expression of CYP11B2 (a key enzyme of aldosterone synthesis) mRNA and caused aldosterone synthesis. CV-11974 (an AT1R antagonist) reduced Ang II-induced aldosterone synthesis, whereas PD-123319 (an AT2R antagonist) had no effect. The concentration of aldosterone peaked earlier than those of monocyte chemoattractant protein-1 (MCP-1) and tumor necrosis factor-α (TNF-α). After 48 h of incubation (under the influence of synthesized aldosterone), CV-11974 and spironolactone significantly reduced the Ang II-enhanced production of MCP-1 and TNF-α, whereas PD-123319 also had no effect. In conclusion, Ang II induces aldosterone synthesis through AT1R and enhances cytokine production through an AT1R-dependent mechanism and, at least partly, through a MR-dependent mechanism in human PBMCs. Keywords:: angiotensin II, aldosterone, peripheral blood mononuclear cell, monocyte chemoattractant protein-1, tumor necrosis factor-α